2016
DOI: 10.1016/j.ebiom.2016.11.010
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomics Predicts Neuroimaging Characteristics of Transient Ischemic Attack Patients

Abstract: BackgroundNeuroimaging is essential for the diagnosis and prognosis of transient ischemic attack (TIA). The discovery of a plasmatic biomarker related to neuroimaging findings is of enormous interest because, despite its relevance, magnetic resonance diffusion weighted imaging (DWI) is not always available in all hospitals that attend to TIA patients.MethodsMetabolomic analyses were performed by liquid chromatography coupled to mass spectrometry in order to establish the metabolomic patterns of positive DWI, D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3
1

Relationship

4
6

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…Region‐specific metabolic alterations as studied in MCAo rats revealed that significant changes in tri‐carboxylic acid (TCA) cycle along with amino acid and nucleotide metabolism occurred specifically in whole cortex and corpus striatum, but not in hippocampus . Significant alterations in neurometabolites such as Cr, cholesterol‐related molecules, threoninyl‐threonine, N‐acetyl‐glucosamine and amino acids have been revealed in acute stroke patients . 1 H magnetic resonance spectroscopy in MCAo model elucidated alteration in metabolites earlier than onset of blood–brain barrier (BBB) damage and in another study within 6 h post‐reperfusion as assessed in cerebrospinal fluid .…”
Section: Discussionmentioning
confidence: 99%
“…Region‐specific metabolic alterations as studied in MCAo rats revealed that significant changes in tri‐carboxylic acid (TCA) cycle along with amino acid and nucleotide metabolism occurred specifically in whole cortex and corpus striatum, but not in hippocampus . Significant alterations in neurometabolites such as Cr, cholesterol‐related molecules, threoninyl‐threonine, N‐acetyl‐glucosamine and amino acids have been revealed in acute stroke patients . 1 H magnetic resonance spectroscopy in MCAo model elucidated alteration in metabolites earlier than onset of blood–brain barrier (BBB) damage and in another study within 6 h post‐reperfusion as assessed in cerebrospinal fluid .…”
Section: Discussionmentioning
confidence: 99%
“…Those patients without contraindications were evaluated by cranial MRI that included diffusion-weighted imaging (DWI) sequences within 7 days of symptom onset. Presence of DWI abnormalities and patterns of acute ischemic lesions were also recorded ( 17 , 28 ).…”
Section: Methodsmentioning
confidence: 99%
“…Those patients without contraindications were evaluated by cranial MRI that included diffusion-weighted imaging (DWI) sequences within 7 days of symptom onset. Presence of DWI abnormalities and patterns of acute ischemic lesions were also recorded 17 24 .…”
Section: Methodsmentioning
confidence: 99%